Os serviços ecossistêmicos como estratégia de governança ambiental: proposição para a gestão do monumento natural Parque Ecológico Serrote do Quinamuiú, em Tauá, Ceará - Nikokavouras, Elpída Andréia de Queiroz (2024)
Ecosystem Services (ES) are essential for human well-being, economic development and the balance of natural ecosystems, providing benefits ranging from water and food provision to climate regulation and cultural and recreational values. These services are, to a large extent, generated and maintained by protected areas, such as Conservation Units (UCs). In this context, UCs stand out as strategic instruments for preserving ecosystems, promoting environmental sustainability and maintaining biodiversity. However, the number of UCs in Brazil, especially in the Caatinga, is insufficient to meet environmental preservation needs. In Ceará, for example, only 5.6% of the Caatinga is protected. Furthermore, the management of these areas faces numerous challenges, such as lack of human and financial resources, low population engagement and conflict of economic interests. Recently, a UC was created entirely within the Caatinga, the Serrote do Quinamuiú Ecological Park Natural Monument, located in Tauá, Ceará, established by Municipal Law No. 2791/2023. Despite its creation, the effective implementation of area management still faces significant challenges. The integration of ES in the management of UCs has emerged as a promising approach to improve Environmental Governance and the effectiveness of management of these protected areas. Therefore, this thesis aimed to analyze the diversity and relevance of ES provided by the Serrote do Quinamuiú Ecological Park Natural Monument, aiming to improve Environmental Governance and management of this unit. The research adopted a methodology that combines bibliographic and documentary research with field research, including unstructured observations and semi-structured interviews with experts. The main results indicate that these areas offer a diverse range of ES, including provision, regulation, maintenance and cultural services, fundamental for human well-being and the balance of local ecosystems. Regarding Environmental Governance, the results indicated that it is still necessary to implement several actions for it to be truly effective. At the end of this thesis, specific strategies were proposed to improve the Environmental Governance of this UC and a Strategic Action Plan for Improving Environmental Management and Governance through the Incorporation of Ecosystem Services. This plan is expected to serve as a model for other UCs, demonstrating that the integration of ES-based approaches can provide substantial environmental, social and economic benefits by bringing improvements in UC management.